INFLUENCE OF REHABILITATION MEASURES ON THE QUALITY AND FULL-VALUE OF THE LIFE OF PATIENTS WITH LOWER LIMB PROSTHESES - Intelehator, Danylo; Khudetsky, Igor; Anotova-Rafi, Yulia (The Ukrainian Scientific Medical Youth Journal, 2021)
Quality and value of life are often recognized as an important indicator for assessing the effectiveness of rehabilitation measures for people with amputation defects of the lower extremities. However, although the topic itself is quite relevant and important, the number of studies that would be devoted to the multiplicity of these factors that directly affect this issue is still quite limited. Such assessments are becoming more and more necessary every year to demonstrate the changes associated with surgical intervention in the anatomical integrity of the human body and the consequences that inevitably occur over time. According to statistics, more than 10,000 amputations are performed in various segments in Ukraine. Analysis of the reasons why people need this operation revealed that most of them (75%) are performed in connection with cardiovascular disease, and more precisely: diabetes, chronic ischemia of the lower extremities, atherosclerosis and endarteritis obliterans. Such grounds for amputation are typical for middle-aged and elderly people. That is why the rehabilitation of these categories of patients after amputation of the lower extremities is determined by significant locomotor disorders that limit a person’s independent movement, self-care, posture disorders, reduced body tolerance to exercise and, consequently, severe limitation of life. Rehabilitation measures for this contingent of persons should be evaluated in terms of social and moral benefits, both for the person with amputation and for people close to him and others. Timely and effective physical rehabilitation also provides significant economic benefits, as it frees up significant costs of resources for the care of special staff, as well as relatives, often forced to leave their professional activities due to the need to care for a loved one. In order to assess the quality of life of patients with lower limb amputation and the impact of rehabilitation measures on these indicators, a study of 32 patients was observed in the rehabilitation center on the basis of the Kyiv State Experimental Prosthetic and Orthopedic Enterprise. In addition to the SF-36 functional assessment questionnaire, the developed Prosthesis Movement Index was tested. The results showed that an individual approach to the rehabilitation process is more effective than working on a typical program without changes in it, as well as the possible convenience of using the index of walking on a prosthesis to assess the effectiveness of mastering the lower limb prosthesis by the patient.